2021
DOI: 10.1039/d0ra08982f
|View full text |Cite
|
Sign up to set email alerts
|

The effects of DOPO modified Co-based metalorganic framework on flame retardancy, stiffness and thermal stability of epoxy resin

Abstract: The DOPO@ZIF-67 promoted the carbonization process of the EP flame retardant composites, and the rigidity and damping coefficient of EP composites are also improved compared with pure EP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…It was shown that MOFs and DOPO have synergistic effects to enhance the smoke suppression performance of the polymer. In addition to the graft modification of DOPO on the original MOFs, some MOFs were coated on DOPO [ 70 , 71 ]. The metal elements in MOFs were also used to promote catalytic carbonization, forming a denser char layer and providing a more effective barrier effect.…”
Section: Hybrid Of Phosphorus–nitrogen Compounds and Mofs As Flame Re...mentioning
confidence: 99%
“…It was shown that MOFs and DOPO have synergistic effects to enhance the smoke suppression performance of the polymer. In addition to the graft modification of DOPO on the original MOFs, some MOFs were coated on DOPO [ 70 , 71 ]. The metal elements in MOFs were also used to promote catalytic carbonization, forming a denser char layer and providing a more effective barrier effect.…”
Section: Hybrid Of Phosphorus–nitrogen Compounds and Mofs As Flame Re...mentioning
confidence: 99%
“…Huang et al [ 23 ] synthesized a nitrogen and phosphorus ionic liquid functional MIL-101-NH 2 and blended it in the epoxy to improve fire safety. Cai et al [ 24 ] made DOPO react with the –C=N– of methylimidazole in a Zn-MOF to raise the flame-retardant quality of epoxy resin (EP). Therefore, in this work, ferric MOFs combined with phosphorous flame retardants were introduced to reduce the flammability of PET.…”
Section: Introductionmentioning
confidence: 99%
“…7 It has been reported that the fiber-reinforced polymer composites (FRPC) have a number of outstanding mechanical properties and some even surpass those of commonly used structural materials, such as steel. 8,9 Commonly used fibers include glass fiber, aramid fiber, carbon fiber, asbestos fiber, boron fiber, and other petroleum-based products, which are difficult to be decomposed through natural processes which will affect the environment and human health. 10,11 While striving to improve the brittleness of the epoxy resin, the production of ecological materials with unique characteristics.…”
Section: Introductionmentioning
confidence: 99%